Indigenous Perspectives at the Core: Addressing Legal Barriers to Sustainable Growth in Indonesia - Riyan Al Fajri (JUSTISI, 2026)
This study aims to analyze the recognition and protection of Indigenous peoples' rights in Indonesia within the context of sustainable development.  The method used in this study is a rigorous normative legal research method using a qualitative approach, focusing on the systematic interpretation of the 1945 Constitution of the Republic of Indonesia and key sectoral laws: Law No. 5/1960 on Basic Agrarian Law, Law No. 41/1999 on Forestry, Law No. 18/2004 on Plantation, and Law No. 6/2014 on Villages. The novelty of this study stems from its integrative approach, which merges normative legal analysis with socio-economic perspectives to explore the multifaceted relationship between Indigenous rights and sustainable development. The results indicate that while formal recognition exists, its implementation is fundamentally impaired by a normative vulnerability in the national legal system. The conclusions of this study state that recognizing and protecting Indigenous rights is crucial for achieving sustainable development goals and recommends the need for accelerated legal recognition, enhancement of the One Map Policy, and better legal protections (including legal aid and mediation platforms) for Indigenous communities.